2019
DOI: 10.1093/jas/skz118
|View full text |Cite
|
Sign up to set email alerts
|

Meta-regression analysis to predict the influence of branched-chain and large neutral amino acids on growth performance of pigs1

Abstract: A meta-analysis was conducted to evaluate the effects of branched-chain amino acids (BCAA), their interactions, and interactions with large neutral amino acids (LNAA) to develop prediction equations for growth performance of pigs. Data from 25 papers, published from 1995 to 2018, for a total of 44 trials and 210 observations were recorded in a database. Diets were reformulated using the NRC (2012) loading values to estimate nutrient concentrations. The response variables were average daily gain (ADG), average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 57 publications
0
13
1
Order By: Relevance
“…However, diets containing HP-DDG in the current study contained not only high Leu concentrations but also adequate levels of Ile and Val based on recommendations from Htoo et al (2017) and Wiltafsky et al (2010) . In addition, using a recently published prediction equation by Cemin et al (2019) , the predicted ADFI of pigs fed HP-DDG was similar to pigs fed CON. Therefore, the reduction of ADFI in Exp.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…However, diets containing HP-DDG in the current study contained not only high Leu concentrations but also adequate levels of Ile and Val based on recommendations from Htoo et al (2017) and Wiltafsky et al (2010) . In addition, using a recently published prediction equation by Cemin et al (2019) , the predicted ADFI of pigs fed HP-DDG was similar to pigs fed CON. Therefore, the reduction of ADFI in Exp.…”
Section: Resultsmentioning
confidence: 67%
“…However, gain efficiency during the first 8 wk was not different between the two dietary treatments. Recently, studies showed that adding corn coproducts to diets may lead to an imbalance of branched chain AA as a result of the high dietary Leu concentration, which can reduce feed intake and, ultimately, growth performance of pigs ( Cemin et al, 2019 ; Kwon et al, 2019 ; Yang et al, 2019 ). However, diets containing HP-DDG in the current study contained not only high Leu concentrations but also adequate levels of Ile and Val based on recommendations from Htoo et al (2017) and Wiltafsky et al (2010) .…”
Section: Resultsmentioning
confidence: 99%
“…Although feed-grade Val was added to the diet to maintain a similar Val:Lys ratio, Val may not have been adequate to counteract increasing Leu. Rather, it may be suggested that diets should also be balanced for Val:Leu to mitigate negative effects on feed intake from increasing Leu as soybean meal or other protein sources (dried distiller’s grains with solubles) are increased in lactation diets ( Cemin et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reducing the ratios of some amino acids, such as tryptophan, valine, or isoleucine, relative to lysine is known to reduce feed intake and growth rate ( Gonçalves et al, 2018 ; Cemin et al, 2019 ). The growth rate is particularly impacted if the leucine to lysine ratio is also high in the diet ( Cemin et al, 2019 ). Diets with high leucine concentrations can be easily produced when corn byproducts from ethanol production are available; however, as stated previously, ethanol byproducts were in short supply during the pandemic.…”
Section: Options Consideredmentioning
confidence: 99%